The End-of-Life Experiences of People with Motor Neuron Disease: Family Carers' Perspectives - Bentley, B.; O'Connor, Moira (Mary Ann Liebert, Inc Publishers, 2016)
Background: People with motor neuron disease (MND) face barriers when accessing palliative care. There is a lack of research about how these barriers affect the end-of-life (EOL) and death experiences of people with MND. Aim: This study examined the perceptions of EOL experiences of family carers of people with MND in Western Australia (WA) to identify unmet needs and gaps in EOL support for people with MND and their family carers. Design: Semistructured interviews were conducted with 12 bereaved family carers of people who died from MND in WA. Thematic analysis was used to identify common themes. Results: The themes identified can be summarized into three main areas: accessing support, accessing information, and feeling prepared. Conclusions: The findings indicate that increased access to specialist palliative care services by people with MND is needed to improve EOL experiences.